Peran Orang Tua Kelompok Masyarakat Kurang Mampu dalam Memastikan Keberlanjutan Studi Anak di Perguruan Tinggi - Bayti Nur Fitria; Raden Roro Nanik Setyowati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Higher education is an important means of improving the quality of human resources, but low-income families often face limitations in ensuring the continuation of their children's studies. This study aims to describe the role of parents in ensuring the continuation of their children's studies at university in low-income families, as well as to identify the driving and inhibiting factors. This study used a qualitative phenomenological approach in Palembon Village, Bojonegoro Regency. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles and Huberman (1984) based on Biddle and Thomas' role theory. The results show that parents play a role in maintaining the continuation of their children's studies, as evidenced by their persistence in seeking sources of educational funding and providing emotional support. The implementation of this role is supported by the child's motivation, family and environmental support, and educational assistance. Meanwhile, economic limitations, income instability, and internal family conditions are inhibiting factors. These findings indicate that despite facing various obstacles, parents continue to actively support the continuation of their children's education at university.